ENGLISH STUDENTS’ SELF-RESILIENCE AND CHALLENGES IN DISTANCE LEARNING - Jumatul Hidayah; Ruly Morganna (International Journal of Research on English Teaching and Applied Linguistics, 2022)
Due to the Covid-19 epidemic, learning has shifted from offline to online, affecting pupils' learning resilience and the complexity of learning obstacles. As a result, the focus of this study is on English students' resilience and the obstacles they experience during distance learning. This study used qualitative methodologies and included 20 English students who were purposefully chosen as participants. They were questioned in accordance with the study's objectives. An interactive model was used to analyse the interview data. The data suggest that in remote learning, students' self-control is lacking. They are under psychological duress. Their physical state was deteriorating, and several of them were experiencing headaches. They are mentally bored and unable to concentrate, and they cannot enjoy learning due to a lack of social interaction. Furthermore, students encounter issues connected to internet signals, budgeting to meet internet demands, and difficulty in locating learning resources during remote learning, all of which are classified as examples of poor technical competence.